Territorial fire statistics and assessment of their causes and consequences on the example of the Rostov region - Ustin, V. G.; Bulygin, Yu. I.; Tretyakov, P. P.; Maslenskiy, V. V. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2020)
Introduction. A deep and comprehensive analysis of the parameters of the situation with fires in the territories of the Russian Federation and its relationship with socio-economic processes is more relevant than ever for Russia. The article presents, summarizes and analyzes statistical data on the situation with fires and their consequences on the territory of the Rostov region for 2018-2019.Problem Statement. The paper considers the problem of official statistical accounting of fires, the procedure for accounting for people killed and injured in a fire in the context of a changing regulatory framework in this area. The analysis of the situation, official and verified information on fires and their consequences will create a reliable socioeconomic characteristic of the Rostov region.Theoretical Part. The paper deals with the peculiarities of accounting of fires and their consequences in Russia. The source materials are the official statistics of the MD of the MES of Russia for the Rostov region on the number of fires on the territory, months, the number of people injured and killed in fires and their distribution by gender, age and time of death, objects and causes of fires.Conclusion. The analysis of fire statistics on the territory of the Rostov region for 2018-2019 is based on official data of the MD of the MES of Russia for the Rostov region, which indicates the reliability of the information provided. Statistical data were evaluated for key factors affecting fire safety: by the number of fires on the territory of the Rostov region, days of the week, months, the number of people injured and killed in the fires and their distribution by gender, age and time of death, objects and causes of fires. Research prospects are outlined.